(untitled) (Fiep Bulletin - online, 2014)
The aim of the present study is centered in establishing the morph functional characteristics, the force of manual hold and the speed of the superior members of integrant Paralympics athletes of the Brazilian Junior Volleyball Team. In Brazil, it is perceived, great lack of studies and information concerning the aspects related to the profile of the Paralympics athletes of this modality. Normally, adaptations and/or formularizations of authors are meet about practitioners of traditional volleyball. For the elaboration of this work a sample of 9 individuals with the average of age of 21,4 ± 2,05 was considered, with the average of height of 1,79 ± 7,76 and the average of the weight without prosthesis was of 63 ± 5,66. All are integrant of the Brazilian Paralympic Junior Team of Seated Volleyball. The tests had been done in 2º World-wide Junior Paralympic Volleyball of 2007. In function of the analysis of the results, we conclude that the current group did not present significant statistical differences in the morph functional characteristics.